Research on QPR and sliding-mode control strategy for three-phase Vienna rectifier - Ma Hui; Yan Shengyang; Wang Shuzheng; Wei Wei (Dianzi Jishu Yingyong, 2019)
Aiming to slove the PI controller′s problem that it is difficult to achieve the fast and accuracy performances of Vienna rectifier， this paper proposed a novel composited nonlinear control strategy with sliding mode controller(SMC) and Quasi proportional resonant(QPR) controller, which can enhance the accuracy performance and the sinusoidal degree of the three-phase currents. In addition, the rapidity and robust performance of DC voltage have also been improved when starting up the rectifier or the load is disturbed. Finally, the MATLAB/Simulink model and experimental platform based on Vienna-type rectifier were built, the results show that the composited control strategy not only has the adventages of the sliding mode control strategy, but also has better robust and dynamic performance. Meanwhile the speed and accuracy of the system have also been greatly improved.